Flow characteristics of groundwater systems: an investigation of hydraulic parameters - Leketa, Khahliso Clifford (University of the Free State, 2011)
The Institute for Groundwater Studies (IGS) undertook a groundwater surface water interaction project under the funding of Water Research Commission starting July 2010. The Modder River was identified as an appropriate study area since it is located downstream of Krugersdrift Dam and has only been impacted by farming activities. This thesis aims at investigating the hydraulic parameters and flow characteristics of groundwater in the study area aquifer so as to have a preliminary picture of the groundwater systems of the site prior to the groundwater surface water interaction project takeoff. The field procedures were performed starting with site inspection, drilling, water level monitoring, pumping tests, tracer tests, and chemical sampling. Geological classification was performed during site inspection and drilling, while soil cover was analysed for texture analysis in the soil science laboratory. Water level monitoring was performed to study the groundwater fluctuations and flow directions with time. Constant rate tests were performed together with recovery tests to determine the transmissivity of the aquifer in the study area while point dilution tracer tests were done to determine the Darcy velocity of the section of maximum flow in the aquifer. In chemical analysis, micro and macro analysis were performed while tritium 3H, Deuterium 2H, and 18-Oxygen were analysed for in isotope analysis. Chemistry and isotope analysis were done to classify water in terms of its source, fate and age. From all boreholes, at the average depth of 8 meters, an alluvial material was obtained in between the top calcareous soil material and the bottom shale formation. The water level fluctuation trend was similar in all boreholes indicating possibilities of a common aquifer intercepted by all boreholes. Using water level time series, groundwater flow direction was determined to be towards the North-Eastern direction slightly in the direction of local topography while the river flow is westwards. The geometric mean of transmissivity values obtained from a Cooper-Jacob plot is 66 m2/d and the geometric mean for the recharge value from chloride method is 1.7 %. The geometric mean of the Darcy velocity value obtained from different boreholes in the aquifer is 6.9 m/d. These mean values are representative of the whole aquifer. In addition to flow direction being due to topography, it is hypothesized that the unusual flow direction behaviour is due to the seepage that acts like a natural borehole at the river bank such that a semi-cone of depression is formed towards the North East. In hydrochemistry, the most abundant cation is sodium followed by magnesium and the most abundant anion is T.Alk (carbonates). From a Piper diagram, groundwater was characterized to be calcium magnesium bicarbonate type of water. The SAR of groundwater is low and within the recommended value for irrigation agriculture while the EC is so high that the water is recommended strictly for crops that are not sensitive to brackish water. According to the isotope analysis, the water from the boreholes and seepage seem to have the same isotopic fingerprint. Needless to say that, the water that seeps on the banks is the same water as that from the aquifer that is intercepted by the boreholes. Groundwater plots closer to the global meteoric water line than river water which plots on the evaporation water line, needless to say that, river water is evaporation water rich in 18-oxygen while groundwater experiences less evaporation hence high 16-oxygen content. The hydrogeology of the area is therefore characterized by the presence of major flow in the gravel material at the average depth of 8 meters.
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2011
Keywords: Groundwater -- South Africa -- Free State; Aquifers -- South Africa -- Free State; Groundwater flow -- South Africa -- Free State -- Measurements; Hydrogeology